The Dental Practice Questionnaire: a patient feedback tool for improving the quality of dental practices. (22nd July 2014) - Narayanan, A; Greco, M
Abstract Background The recently introduced Practice Accreditation Scheme as part of the Australian National Safety and Quality Health Service (NSQHS) standards raises the question of how dental practices can implement valid and reliable patient experience feedback mechanisms for performance evaluation and enhancement. This article describes the development and use of a dental patient questionnaire (DPQ) that can be used for this purpose. Methods DPQ was piloted on 58 voluntary dental practices across Australia and resulted in an average of just over 50 patient responses to 35 practices returned. Statistical properties of the DPQ were tested through validity (construct, content and criterion), structural integrity and reliability measurements. Results DPQ is valid and reliable, with statistical analysis showing that there are significant differences in patients' scores depending on their age, gender, regularity of visit and number of years attending the practice. Two patient satisfaction models were derived. However, there may be scope for improving DPQ to more effectively produce patient feedback on summative aspects of services provided by dental practices. Conclusions DPQ has been shown to be 'fit for purpose' in its first pilot and may prove to be a useful tool for supporting dental practices in the Practice Accreditation Scheme.